Efek Hepatoprotektif Infus Daun Sukun (Artocarpus altilis (Park) Fsb) Terhadap Kerusakan Hati Tikus yang Diinduksi dengan Karbon Tetraklorida - K.J, Wahyu Atmaja; Sari, Santi Purna; Azizahwati, Azizahwati (Majalah Ilmu Kefarmasian, 2010)
Breadfruit leaves (Artocarpus altilis (Park.) Fsb.) are used as traditional medicine in treatment of liver diseases. This study aimed to figure out the hepatoprotective effect of breadfruit leaves infusion in carbon tetrachloride-induced liver damage in male albino rats. The study used 25 male albino rats of Sprague-Dawley strain, which were divided randomly into five groups. Group I (normal control group) and group II (carbon tetrachloride-induced control group) only received 0,5% carboxymethylcellulose (CMC) solution. Group III-V received different dose of breadfruit leaves infusion for seven days respectively, which were 13,5 g/kgBW (dose 1), 27 g/kg BW (dose 2) and 54 g/kg BW (dose 3). On 7th day, all groups, excepted the normal group, were induced by 0,4 ml/kgBW dose of carbon tetrachloride perorally two hours after the last breadfruit leaves infusion given. Parameters of liver damage were estimated by measuring the activity of plasma alanine aminotransferase (ALT), the concentration of lipid peroxide in liver, and the concentration of lipid peroxide in plasma. The results of ANOVA (p<0,05) demonstrated that breadfruit leaves infusion at a dose of 54 g/kgBW (dose 3) consumed for seven days respectively before 0,4 ml/kgBW dose of carbon tetrachloride-induced had hepatoprotective effect estimated by the activity of plasma ALT and the concentration of lipid peroxide in liver.